Hysteretic Behavior of Steel Column Strengthened With CFRP in Thermal Environment - Zhen-Guo Li (Indonesian Journal of Electrical Engineering and Computer Science, 2012)
This paper is concerned with analysis for the strengthening effect of carbon fiber-reinforced polymer (CFRP) on steel columns under cyclic lateral loading in thermal environment. Based on the finite element theory of thermo-elastic problem and steel structure stability theory, the hysteretic behavior of axial compression steel columns was studied by using Ansys software. The main variables investigated are:  cyclic lateral loading, temperature, axial compression ratio and ductility. The results show that the CFRP wraps can improve the ultimate cyclic lateral loading and ductility of steel columns prominently in thermal environment which benefit to the anti-seismic capacity of steel structure. The effect of axial compression ratio on ultimate cyclic lateral loading is very obvious, more enhancements achieved with the axial compression ratio increased. While effect of temperature on ultimate cyclic lateral loading is not very obvious below 300℃. DOI: http://dx.doi.org/10.11591/telkomnika.v10i5.1278